Contribution from SOIR/VEX to the updated Venus International Reference Atmosphere (VIRA). Issue 1 (1st January 2016) - Vandaele, A.C.; Chamberlain, S.; Mahieux, A.; Ristic, B.; Robert, S.; Thomas, I.; Trompet, L.; Wilquet, V.; Belyaev, D.; Fedorova, A.; Korablev, O.; Bertaux, J.L.
Highlights: SOIR improves next generation VIRA by providing high-resolution vertical profiles. The SOIR data set covers CO2, CO, HCl, HF, H2 0, SO2, aerosol and temperature. Latitudinal variability is investigated and compared to the current content of VIRA. Temperature at the terminator are shown to differ from day/night profiles. Abstract: The SOIR instrument on-board Venus Express is an infrared spectrometer covering the 2.2–4.3 μm spectral region. This instrument allows the detection of several key species of the Venus atmosphere, including CO2, CO, H2 O/HDO, HCl, HF and SO2 . From the CO2 density measurements, temperature is inferred giving information on the thermal structure of the atmosphere. Here we described the kind of data (profiles, latitudinal average, etc.) that will be provided to the updated VIRA compilation.